Partition of horseradish peroxidase with maintained activity in aqueous biphasic system based on ionic liquid - Cao, Qing; Quan, Li; He, Chiyang; Li, Na; Li, Kean; Liu, Feng (Talanta, 2008)
Enzyme activity and partition behavior in aqueous biphasic systems (ABSs) consisting of ionic liquid (IL) and salt (IL-ABSs) were investigated to increase our understanding of IL-ABSs and shed light on their application potential as enzyme extraction system. With horseradish peroxidase (HRP) as the model enzyme, several effects of alkylimidazolium chloride-K2HPO4 ABSs on activity and partition behavior of enzyme were studied including alkyl chain length of ILs and concentrations of each component. High lyotropic ILs (1-butyl-3-methylimidazolium and 1-ethyl-3-methylimidazolium chloride) and adequate water content (>40%) were both essential for the activity maintenance of HRP in IL-ABS. 1-Butyl-3-methylimidazolium chloride ([C(4)mim]Cl) was found to be an appropriate IL for phase forming and HRP activity retaining. After optimization of phase condition, about 80% HRP amount was distributed in the IL-rich upper phase, and greater than 90% enzyme activity was obtained. Moreover, compared with the commonly used polymer-based ABSs, this [C(4)mim]Cl-ABS has a much lower viscosity, which is very beneficial to the experimental operation. Therefore, the tested IL-ABS could be considered as a potential enzyme extraction system. (C) 2008 Elsevier B.V. All rights reserved. Chemistry, Analytical SCI(E) EI PubMed 30 ARTICLE 1 160-165 77